Regulating difference : religious diversity and nationhood in the secular west - Burchardt, Marian (Rutgers University Press, 2020)
"Transnational migration has contributed to the rise of religious diversity and has led to profound changes in the religious make-up of society across the Western world. As a result, societies and nation-states have faced the challenge of crafting ways to bring new religious communities into existing institutions and the legal frameworks. Regulating Difference explores how the state regulates religious diversity and examines the processes whereby religious diversity and expression becomes part of administrative landscapes of nation-states and people's everyday lives. Arguing that concepts of nationhood are key to understanding the governance of religious diversity, Regulating Difference employs a transatlantic comparison of the Spanish region of Catalonia and the Canadian province of Quebec to show how processes of nation-building, religious heritage-making and the mobilization of divergent interpretations of secularism are co-implicated in shaping religious diversity. It argues that religious diversity has become central for governing national and urban spaces"--